Legitimasi dan Perlindungan Hukum Nadzir terhadap Klaim Ahli Waris; Studi Kasus di Kota Semarang - Arta Brilyan Musika; Suhadi Suhadi (IAIN Langsa, 2025)
This research aims to analyze the legitimacy and legal protection of nazhir in facing inheritance claims over waqf land in Semarang City. The study focuses on the extent to which the position of nazhir is protected under Indonesian positive law and how the implementation of waqf regulations ensures legal certainty over waqf assets, which serve a strategic function for public welfare. The research methodology employs a normative-juridical approach by examining legislation, legal doctrines, and religious court decisions, including Decision No. 227/Pdt.G/2024/PTA.Smg. The findings indicate that although nazhir gains legitimacy through Law No. 41 of 2004 and its derivative regulations, legal protection remains weak when administrative documents such as the Waqf Pledge Deed (AIW) and waqf land certificates are not fulfilled. This situation triggers vulnerability to inheritance claims, thereby necessitating institutional strengthening of nazhir and legal reforms to guarantee the principle of non-alienation of waqf assets and consistency in judicial practice.